Pendugaan Umur Simpan Sale Lilit Menggunakan Metode Accelerated Shelf-Life Testing (ASLT) Model Arrhenius: Estimating The Shelf Life of Sale Lilit Using the Arrhenius Model Accelerated Shelf-Life Testing (ASLT) Method - Ruhaeni, Ruhaeni; Zainuri, Zainuri; Utama, Qabul Dinanta (Universitas Bumigora, 2025)
Indonesia is one of the countries with great potential, especially in the agricultural sector. One of the most widely used agricultural commodities is types of fruits such as bananas. Sale lilit is one of the processed foods with the main ingredient in the form of ripe bananas that have been dried and then processed and packaged using aluminum foil packaging. This study aims to examine the estimated shelf life of sale lilit. The method of estimating the shelf life used is the Accelerated Shelf-Life Testing (ASLT) method of the Arrhenius model. Sale lilit is stored at three different storage temperatures according to the treatment (30°C, 40°C and 50°C). Parameters observed include moisture content, FFA content, texture (hardness and crispness), color, aroma, taste and texture. These parameters were analyzed during storage at dat 0, 5, 10, 15 and day 20 of storage. The results showed that sale lilit stored at 30°C has the longest shelf life. Based on data on the rate of increase in FFA levels, the estimated shelf life of the sale is 56,119 days. This study implies that storage temperature plays an important role in extending the shelf life of sale lilit, so producers can optimize storage conditions, packaging, and product distribution.